2012
DOI: 10.1093/ndt/gfr755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioartificial renal tubule device prepared with lifespan-extended human renal proximal tubular epithelial cells

Abstract: BTD treatment results in less damage from endotoxin shock and increased life span in AKI goats. These results suggest that BTD may be a useful component of bioartificial kidneys and should be considered in the next generation of renal replacement therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…Here, we studied release of IL‐6, IL‐8 and IL‐10 from the bioreactor after perfusion with 10 μg/ml of LPS for 24 hrs or after perfusion with normal medium not containing LPS. LPS administration was performed in two of the previous in vivo studies where changes in cytokine levels were observed and one study used E. coli administration. The conditions under which the other in vivo studies and the clinical trial were performed could not be mimicked in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we studied release of IL‐6, IL‐8 and IL‐10 from the bioreactor after perfusion with 10 μg/ml of LPS for 24 hrs or after perfusion with normal medium not containing LPS. LPS administration was performed in two of the previous in vivo studies where changes in cytokine levels were observed and one study used E. coli administration. The conditions under which the other in vivo studies and the clinical trial were performed could not be mimicked in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine levels in serum and plasma were measured in various animal studies and the Phase I/II clinical trial . Some changes in cytokine levels suggested that beneficial effects of BAK treatment might be a result of immunomodulatory functions . However, the release of cytokines or other immunomodulators from the bioreactor unit has not been investigated, so far.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that levels of serum cytokines, such as TNF-α and IL-6, are increased in patients with severe AKI [1416]. Pro-inflammatory cytokines may contribute to additional organ dysfunction, which is associated with high mortality [17].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, clinical trials using this approach reported better survival and more rapid recovery from AKI [69,70]. Saito et al also reported a bioartificial renal tubule device that reduces the expression levels of inflammatory cytokines and increased the life span of AKI goats [71]. These results suggest bioartificial devices may diminish the morbidity and mortality of AKI patients [72,73], but the type(s) of renal tubule cells used needs further consideration.…”
Section: Bioartificial Kidneymentioning
confidence: 99%